Efektivitas Model Pembelajaran Project Based Learning (PjBL) terhadap Minat dan Hasil Belajar Siswa - Isrohani Hamidah; Sinta Yulia Citra (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model on student interest and learning outcomes at SMA Negeri 4 Seluma. The method used is a quasi-experimental (Quasi Experiment) with a randomized control group pretest-posttest design. The results showed that students' interest and learning outcomes in the experimental class (XI IPA 1) were higher than the control class (XI IPA 2) with a Sig. (2-tailed) of 0.000. In conclusion, the Project Based Learning (PjBL) model is effectively used as a learning model for students' interest and learning outcomes in biology at school. Keywords: Learning Outcomes, Interest in Learning, Project Based Learning